The Cid Way: An example of tourism good practices: Evolution and current tourism situation - Azuara Grande, Alberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The increase of activities linked to cultural tourism has been a constant in recent decades. One of these new forms of tourism is based on traveling cultural routes, as the Spanish case of the Cid Way, developed at institutional level as an initiative of regional councils. The main objective of this work is to present the evolution and current situation of the Camino del Cid. Furthermore, implementation of this cultural route in the territory and impacts that it is generating are analysed, from the perspective of sustainable tourism.